1990
DOI: 10.3758/bf03208161
|View full text |Cite
|
Sign up to set email alerts
|

Temporal order and tactile patterns

Abstract: Temporal order judgments (TOJs) were obtained for tactile stimuli presented to subjects' fingerpads. In one set of measurements, pairs of spatial patterns were presented successively to a single fingerpad (same-site condition), to two fingers on the same hand (ipsilateral condition), or to two fingers on opposite hands (bilateral condition). The subjects were instructed to report which one of the two patterns was presented first. TOJs were more accurate in the same-site condition than in either the ipsilateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
40
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 18 publications
5
40
0
Order By: Relevance
“…Second, the requirement that subjects be able to both identify the patterns and judge the order in which they were delivered likely increases the cognitive complexity of the task, which, in turn, may reveal greater differences due to age. Results from earlier studies indicate that the localization task is less demanding: The thresholds for this task (Sherrick, 1970) are considerably shorter than the thresholds for patterns when, in the latter case, subjects had to both identify the patterns and report them in the correct temporal order (Craig & Xu, 1990). In addition, one of the tasks in the present study required the subjects to correctly report the order of four patterns, adding an additional cognitive load.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…Second, the requirement that subjects be able to both identify the patterns and judge the order in which they were delivered likely increases the cognitive complexity of the task, which, in turn, may reveal greater differences due to age. Results from earlier studies indicate that the localization task is less demanding: The thresholds for this task (Sherrick, 1970) are considerably shorter than the thresholds for patterns when, in the latter case, subjects had to both identify the patterns and report them in the correct temporal order (Craig & Xu, 1990). In addition, one of the tasks in the present study required the subjects to correctly report the order of four patterns, adding an additional cognitive load.…”
mentioning
confidence: 78%
“…This appeared to be the case for many of the younger subjects. For that reason, and because 75% correct has been used in previous studies of temporal order with patterned stimuli (Craig & Xu, 1990), we also calculated 75% thresholds for the 2-ID.B condition (see Table 2). Again, the older subjects showed significantly longer SOAs (Z 6.04, p .001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was tested using one finger, two fingers of the same hand, or fingers of two hands [16]. But recently, Yamamoto and Kitazawa revealed that the judgement of the temporal ordering of taps in the bilateral condition was reversed from the mere fact of crossing one's arms, and furthermore found that the effect could be cancelled when holding sticks that crossed to 'undo' the crossing of the arms!…”
Section: Temporal Orderingmentioning
confidence: 99%
“…but not when pairs are presented to separate fingers (Craig & Xu, 1990). Finally, temporal masking declines when pairs of patterns are presented to separate fingers instead of a single finger (Craig, 1983).…”
mentioning
confidence: 98%